1998
DOI: 10.1097/00006676-199805000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Krev-1 Expression Inhibits the Growth of Pancreatic Adenocarcinoma Cells

Abstract: Pancreatic ductal adenocarcinoma is characterized by a high rate of activating mutations involving codon 12 of the K-ras protooncogene. As a means of ras-targeted intervention, the effects of enhanced Krev-1 gene expression on the growth and tumorigenicity of the hamster pancreatic adenocarcinoma cell line PC-I were evaluated. Overexpression of the Krev-1 gene product resulted in morphologic reversion to a less transformed phenotype, as well as retarded growth kinetics and diminished potential for anchorage-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These inhibitors mimic the prenyl group substrate or the tetrapeptide recognition sequence on ras that is targeted by farnesyltransferase (known as CAAX motif; cysteine, aliphatic, aliphatic, X). Several studies have shown that inhibition of ras signaling alter the growth of pancreatic cancer cell lines (Leach et al, 1998;Shichinohe et al, 1996;Song et al, 2000). In this study, we selected two pancreatic cancer cell lines: one with wild type K-ras and the other with mutant K-ras.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors mimic the prenyl group substrate or the tetrapeptide recognition sequence on ras that is targeted by farnesyltransferase (known as CAAX motif; cysteine, aliphatic, aliphatic, X). Several studies have shown that inhibition of ras signaling alter the growth of pancreatic cancer cell lines (Leach et al, 1998;Shichinohe et al, 1996;Song et al, 2000). In this study, we selected two pancreatic cancer cell lines: one with wild type K-ras and the other with mutant K-ras.…”
Section: Discussionmentioning
confidence: 99%
“…5C), but not an increase in progression to adenocarcinoma. As Rap1 was originally identified as Krev (Kirsten ras revertant 1), a GTPase whose activity reversed Ras-induced transformation (Sakoda et al, 1992) and inhibited the development of multiple forms of adenocarcinoma (Burney et al, 1994;Damak et al, 1996;Leach et al, 1998), and because KRIT1 is upregulated during cAMPstimulated reversal of Ras-mediated cell transformation (Bachrati et al, 1999), it will be of interest in future studies to examine whether the increase in adenoma number is the result of an effect on tumor initiation/transformation downstream of nuclear -catenin signaling.…”
Section: Apcmentioning
confidence: 99%
“…Other useful models for studying the growth-regulatory effects of TGF-␤ in pancreas are provided by several transformed cell lines derived from human pancreatic cancers or chemically induced tumors from experimental animals. For example, several of these exocrine pancreatic cell lines are responsive to TGF-␤ peptides and can be used for in vitro anchoragedependent and -independent cell growth assays (5,20,33,41,43,45,46,51,55,72,83). In addition, because these cells often carry complex genetic alterations, including mutations in several mediators of TGF-␤ signaling, the results obtained from using these lines can be informative when dissecting specific defects in this pathway (5,23,33,83,85).…”
Section: Exocrine Pancreatic Epithelial Cells Are a Useful Model For mentioning
confidence: 99%